ADVERSE EVENT NOTIFICATION ANALYSIS THROUGH PATIENT SAFETY CULTURE RESEARCH - Barbosa Teodoro, Roberta Flecher; Silva, Alexandre Sousa da [UNESP]; Carreiro, Monica de Almeida; Bilio, Rafael de Lima; Paula, Danielle Galdino de (Univ Federal Estado Rio De Janeiro, Programa Pos-graduacao & Enfermagem, 2020)
Objective: To evaluate the patient's safety culture allows hospitals to identify and manage relevant safety issues preventively through their work routines. Method: A quantitative, transversal and descriptive study, carried out in 2017 at the Adult Intensive Care Unit in a private hospital, located in Niteroi / RJ. The population were medical professionals and nursing staff. Statistical analysis was conducted using program R, with the Rcmdr interface. Results: Patient Safety Culture Survey questions about event notification applied to 97 professionals had a response rate of 85.6%, corresponding to 83 professionals. Less than 45% of respondents reported an error, deception, or failure, affecting the patient, 59.0% did not file reports in the last 12 months prior to the survey, and there was no significant difference in the amount of notifications regardless of professional category or level of education. Discussion: Those with longer hospital time and with more time in that intensive therapy were more likely to file reports. There was no correlation between the number of reports filed with the time in profession and the workload. Conclusion: With regard to the awareness of the need to report adverse events, the analysis performed contributed to the improvement of patient safety.
Keywords: Patient safety; Culture; Intensive care unit; Nursing; Notification of adverse events